Resistência à compressão de prismas preenchidos com argamassa / graute - Marco, Carlos Eduardo Giacomini de (2016)
This work has as main objective to analyze the mechanical behavior of prisms run with ceramic bricks and filled with mortar or grout, checking their influence when subjected to centric compression. An experimental program consists of four different types of prisms was developed. They were used for making the prisms blocks of three different Manufacturers. The ceramics were randomly named as Manufacturer 1 Manufacturer 2 and Manufacturer 3, manufacturers have provided the following resistance of structural blocks: Manufacturer 1 - fbk (A) 6 MPa, Manufacturer 2 - fbk (E) 7 MPa and fbk (C) 15 MPa Manufacturer 3 - FBK (B) and 6 MPa FBK (D) 15 MPa.The prisms were molded with industrialized mortar. Each prism type with its respective resistors blocks were molded as follows: hollow prism, prisms filled with grout (the larger castings), the same used in the settlement, and prisms filled with grout, totaling 320 prisms, which were subjected to tests to simple axial compression. The results were analyzed statistically by the Tukey test at 5% significance level. It was concluded that the grout used not added significant increase in resistance to the prisms, the study can not say whether it is possible or not to replace the grout by mortar, to fill the cast, as well as adequate strength of the mortar used in filling It should be further studied.